Application of the Plan, Do, Check, and Act Cycle in the Management of Nursing Services in Disasters: The Case of a University Hospital - Boduç, Naile; Karadede, Özkan; Şen, Ahmet; Budak, Beyhan (Cerrahpaşa Medical Journal, 2023)
In recent years, the incidence of disasters has increased worldwide due to various reasons, particularly climate change, resulting in death, injury, economic loss, and environmental damage. Recent large-scale earthquakes have reaffirmed that Turkey is a country with high disaster risk. It is possible to prevent or reduce deaths, injuries, and epidemics after disasters by planning before, during, and after disasters. For the sustainability of nursing services in disasters, executive nurses should effectively perform management functions related to planning, organizing, directing, coordinating, and controlling. This study examines the nursing services provided at a university hospital where earthquake victims were transferred following the Kahramanmaraş earthquake that impacted 11 provinces on February 6, 2023. The study uses the Plan, Do, Check, and Act cycle to present the nursing activities, aiming to contribute to disaster nursing literature and guide executive nurses. Cite this article as: Boduç N, Karadede Ö, Şen A, Budak B. Application of the PDCA cycle in the management of nursing services in disasters: The case of a university hospital. Cerrahpaşa Med J 2023;47(S1):78-82.